If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-6x-6x)=12
We move all terms to the left:
(-6x-6x)-(12)=0
We add all the numbers together, and all the variables
(-12x)-12=0
We get rid of parentheses
-12x-12=0
We move all terms containing x to the left, all other terms to the right
-12x=12
x=12/-12
x=-1
| 4(7x-1)+3(2-5x)=4(3x+5) | | 9w-11w=-14 | | 3(t^2-6t+5)=0 | | (8x+4)+x=47 | | 3/k=4/5 | | 6y+2y-7=9 | | 2(4x+2)=4x-10(x-1) | | 5y+2=3y+7=13y-31 | | 127a−3=2a+12=a= | | (8x+4)x=47 | | 1.8+0.2y=5.8 | | (11x+11)+x=37 | | 15-5x=20-7x | | 8x=6/7 | | –10j−8=–9j | | (3x+3)+x=66 | | 78=4-7(3x+3)+2x | | -5(u-3)=-3u+21 | | 10n-2=9n | | 0.5x-0.6=0.4x=8 | | 4(2x+5)+2x+3=-11 | | 4n+6-2n=2+3 | | x4+4=66 | | x+0.25=18.75 | | -4x-7=x-2 | | X+6(-3x)=38 | | 7x+6x=-8(-7x-8)+6(1-6x) | | 3+5a=-73+5a=−7 | | 8-5n=3n-6n | | 7x+38=180 | | X-0.7x=168 | | 1/4b–2=–1/2b+4 |